MODEL FISIK SKALA PENUH KONSTRUKSI TANGGUL DAN PINTU KLEP DALAM UPAYA PENANGGULANGAN BENCANA GENANGAN AIR PASANG SURUT PERKEBUNAN KELAPA DALAM BERBASIS KEARIFAN LOKAL - Ari Sandhyavitri (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2017)
The problem of coconut plantation in Indragiri Hilir Regency especially in Gaung Anak Serka District is water puddle that inundated coconut plantation due to tidal effect causing the productivity of coconut plantation to decrease. Until now there has been no good solution other than the improvement of the air conditioning trio, embankment, valve door and channel (secundary channel). Based on survey results that have been done the problem of the arrival of air puddles that inundated this coconut plant is damaged or damaged embankment that protect coconut garden from water channeled. The water that inundated the coconut plantations already contains salinity due to mingling with sea water. At the time of the air tidal air pressure that continues to hit the wall of the goruling dike becomes eroded. This research describes how the mitigation of the impact of existing problems is by designing the construction of dikes and valve doors using coconut wood composite that is widely available in Indragiri Hilir area. The coconut wood is used as a substitution material to strengthen the embankment structure and the door of the valve. Utilization of coconut wood composite technology with technical and environmental quality can be one of the solutions needed to improve the productivity of coconut plantations.